The elephant in the room: a study on the dialogue about sexuality during Assisted Reproductive Technology visits - Michele Montecalvo; Elena Vegni; Raffaella Balestrieri; Daniela Leone; Lidia Borghi (Taylor & Francis Group, 2024)
Despite ongoing medical advancements in infertility treatment, the significant impact of sexuality on this journey often goes unaddressed. The present research aims to examine sexual conversations during ART visits, including who initiate the conversation and their content.This quali-quantitative study delves into analyzed video-recorded ART visits to explore how "sex" conversations are broached during healthcare interactions. Our findings reveal a strikingly low proportion of utterances related to sexuality, accounting for only 1.3% of the total 14,372 utterances analyzed. Sex utterances were mainly introduced by physicians (72%), while regarding those introduced by the couple, 64% were reported by men. From the qualitative analysis on the utterances emerged three distinct levels of communication about sex: explicit, almost explicit, and implicit. While physicians and males exhibit an almost balanced distribution across the 3 levels, female patients primarily respond to explicit and almost explicit communication initiated by physicians. The low percentage of sexual utterances underscores the rarity of these conversations during ART interactions, despite the clinical field where sexual health should deserve a crucial attention. Opening the door to conversations about sexuality could help to create a safe and supportive space for patients to talk about sex, with a potential impact on well-being and quality of care during the ART process.